Unveiling the Role of Business Freedom to Determine Environmental Degradation in Developing Countries - Audi, Marc; Ali, Amjad (International Journal of Energy Economics and Policy, 2023)
Presently, environmental degradation is the prime concern of the world economies as a whole. Following this concern, Sustainable Development Goals designed by the UNDP raise the slogan “Clear Environment for All”. This paper has analyzed the impact of business freedom on environmental degradation in the case of 110 developing countries from 2000 to 2020. Panel least squares and generalized moments methods have been applied to check the impact of explanatory variables on dependent variables. The results show that business freedom and renewable energy consumption have a negative and significant impact on environmental degradation in selected developing countries. The results explain that financial development has a positive and significant impact on environmental degradation in developing countries. Whereas urbanization has a positive and significant impact on environmental degradation. Thus, for the reduction of environmental degradation business freedom and renewable energy consumption should be promoted, whereas negative linkages of urbanization and financial development should be reduced.